ЗАДЫХАЮЩИЙСЯ БЛОК. ЧАСТЬ 1 - Л. И. Дворецкий (SINAPS LLC, 2014)
In the article the author makes an attempt to reconstruct the history of the disease of the Russian poet A.A. Block on the basis of correspondence, memoirs of contemporaries, doctors who watched the poet. Medical issues diseases of the poet are discussed taking into account the historical situation, which has had some extent, the impact on the tactics of the patient.